(untitled) (Journal of Parents and Teachers, 2012)
Socrates was a teacher but not because he decided to be a teacher but because with his life, he achieve that with a daily meeting could be a perfect oportunity to look for the truth talking with others. Socrates did not have, therefore, pupils but disciples: young people who approached him in orfer to receive his knowledge, to learn his way of understanding life and living it, even of losing it because he died because of his commitment with the search of the good and the truth.